2 - The Hybrid Administrator-scholar Paradigm in Higher Education Leadership in Africa - Zhou, Sindiso (Journal of Higher Education in Africa, 2022)
The higher education landscape has been in a state of flux since the turn of the twenty-first century owing to pressure to internationalise and adopt entrepreneurial approaches in response to global demands. These exigencies have not spared middle-level managers in the academy who straddle the divide between administration and scholarship. This article explores the administrator-scholar paradigm in the context of the globalisation momentum in the academy, using an autoethnographical approach, in which I examine my personal and professional experience as a department chair in two universities over a period of five years. The study pays particular attention to how the dual role was enacted and views the administrator-scholar phenomenon as a resource, not a problem, as explicated in existing research. I articulate the leadership qualities that middle-level managers – more particularly, heads of departments – need, to navigate the contested space and ambivalent landscape of higher education leadership. Institutional gaps and the absence of systemic socialisation led me to develop a domain acculturation model, Divergent Collaborative Leadership, which emphasises the administrator- scholar in the construction of professional identities in higher education in the African context.